Weighted approximation by generalized Baskakov operators reproducing affine functions - Jorge Bustamante (Modern Mathematical Methods)
Some extension of the Baskakov operators are introduced. The new operators reproduce affine functions. The rate of convergence of the associated approximation process is obtained in polynomial type weighted spaces. A Voronovskaja type result is included.